Analysis of the Effect of Biodiesel Use on the Wear of Heavy Equipment Machinery Components in the Mining Industry - Gede Arya Rachman; Syukri M. Nur (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
This study analyzes the effect of the use of B30/B35 biodiesel on the wear of heavy equipment engine components in the Indonesian mining industry. Through a longitudinal experimental design for 12 months, the study was conducted on 24 units of heavy equipment consisting of excavators, bulldozers, and articulated dump trucks in three different mining locations: a coal mine in East Kalimantan, a nickel mine in Southeast Sulawesi, and a gold mine in Papua. The results show that the use of B30/B35 biodiesel consistently reduces the wear rate of components compared to conventional diesel. Nozzle injector wear in the biodiesel group is 18.6% lower, piston ring wear is 15.3% lower, cylinder liner wear is 12.7% lower, and bearing wear is 14.2% lower. SEM and EDS analysis revealed that biodiesel forms a tribochemical layer on metal surfaces that reduces direct contact between surfaces and minimizes wear. The analysis of the lubricant showed lower concentration of metal particles and better lubricant quality parameters in the biodiesel group. The developed predictive model indicates an extension of component life of around 15-20% with the use of biodiesel, potentially providing maintenance cost savings of 12-18% per year. These findings change the perception that the use of biodiesel is solely regulatory compliance, to an operational strategy that provides economic and technical benefits. This study provides a scientific basis for the optimization of preventive maintenance programs for mining heavy equipment that uses biodiesel and supports the sustainability of the implementation of the national mandatory biodiesel policy.